The internet as magnifying glass - Matei, Sorin (Javnost (Ljubljana), 2003)
The article investigates the relationship between real and virtual social spaces and the role marital status plays in mediating it. Marital status is used as an indicator for emergence of "loose connections" in American society.The study employs survey data collected from 1812 Los Angeles residents. Data analysis by logistic regression and analysis of variance indicates that although singles find the Internet more attractive, due to its social capabilities (e.g., making new friends), it is married individuals that benefit the most from having on-line ties. The general conclusion is that integration of Internet technologies in social life is steered by off-line social contexts. Singles, who have weaker social ties and lower level of commitment to formal and informal organisations, instinctively see the Internet as a social opportunity. Yet, they will be far less successful in taking advantage of this opportunity than married individuals are. Married individuals benefit from what appears to be the Internet's "magnifying glass" effect: strong personal bonds in reality are strengthened by making Internet friends.
Keywords: družbene skupine; zakonski stan; social psychology; socialna psihologija; communication; komuniciranje; računalniške komunikacije; internet; prostor (sociologija)